2007
DOI: 10.1016/j.febslet.2007.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in DIIS5 and the DIIS4–S5 linker ofDrosophila melanogastersodium channel define binding domains for pyrethroids and DDT

Abstract: Mutations in the DIIS4-S5 linker and DIIS5 have identified hotspots of pyrethroid and DDT interaction with the Drosophila para sodium channel. Wild-type and mutant channels were expressed in Xenopus oocytes and subjected to voltageclamp analysis. Substitutions L914I, M918T, L925I, T929I and C933A decreased deltamethrin potency, M918T, L925I and T929I decreased permethrin potency and T929I, L925I and I936V decreased fenfluthrin potency. DDT potency was unaffected by M918T, but abolished by T929I and reduced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
144
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(157 citation statements)
references
References 20 publications
10
144
0
3
Order By: Relevance
“…This model predicts that pyrethroids bind to the lipid-exposed interface formed by the linker helix connecting S4 and S5 in domain II (IIL45), and helices IIIS6 and IIS5 (the IIL45-IIS5-IIIS6 triangle model or site 1 hereinafter). Experimental data from systematic site-directed mutagenesis studies in these regions support this model (16,17). Several key kd mutations in IIL45, IIS5, and IIIS6 are predicted to confer resistance by altering pyrethroid binding (18,19).…”
mentioning
confidence: 65%
“…This model predicts that pyrethroids bind to the lipid-exposed interface formed by the linker helix connecting S4 and S5 in domain II (IIL45), and helices IIIS6 and IIS5 (the IIL45-IIS5-IIIS6 triangle model or site 1 hereinafter). Experimental data from systematic site-directed mutagenesis studies in these regions support this model (16,17). Several key kd mutations in IIL45, IIS5, and IIIS6 are predicted to confer resistance by altering pyrethroid binding (18,19).…”
mentioning
confidence: 65%
“…The role of domain II in promoting activation is demonstrated by the effect of ␤-scorpion toxin and insecticides, which have been shown to bind to S1-S2 and S3-S4 or S4 -S5 and S5 sections of domain II in Drosophila sodium channels and Na v 1.4, stabilizing the voltage sensor in its activated state (55,56). The voltage dependence of the toxin-modified channel is shifted to more negative potentials.…”
Section: Discussionmentioning
confidence: 99%
“…Although no superkdr mutation has so far been identified in mosquitoes, it was suggested that Leu932Phe, in association with Ile936Val (both also in the IIS4-S5 linker), in Culex might play this role, being the first example of super-kdr in this group (T. G. Davies et al, 2007a). Accordingly, these sites have proved to be important for the interaction between Na V , in the D. melanogaster sodium channel and pyrethroids or DDT (Usherwood et al, 2007). Substitutions in site 929 are also involved in enhanced pyrethroid resistance, as is the case with the Lepidoptera Plutella xylostella mutation Thr929Ile, detected in association with Leu1014Phe (Schuler et al, 1998).…”
Section: The Kdr Mutationmentioning
confidence: 99%